Vicarious liability, non-delegable duty and the Ng Huat Seng decision - Low, Kee Yang (Institutional Knowledge at Singapore Management University, 2017)
In recent times, courts in Singapore and elsewhere have been grappling with the issue of delegability of duty of care. In the process, they have vigorously defended the conventional position that a duty of care is, in general, delegable. Accordingly, attempts at broadening the ambit of vicarious liability and non-delegable duty, respectively, have been carefully scrutinized. The recent Singapore Court of Appeal decision of Ng Huat Seng v Munib Mohammad Madni adds to the judicial thinking on this complicated and controversial subject.